Psychometric Properties of the Rosenberg Self-Esteem Scale: A Specific Application to People with Diabetes Mellitus - Widiana, Herlina Siwi; Urbayatun, Siti; Azizah, Putri Nur (Journal of Educational, Health and Community Psychology, 2025)
Self-esteem is a critical psychological component for individuals living with diabetes mellitus, especially in supporting effective self-management behaviors. Accordingly, the use of a self-esteem assessment instrument with robust psychometric qualities is essential to support effective self-management among individuals with diabetes mellitus. This study aims to evaluate the psychometric characteristics of the Rosenberg Self-Esteem Scale by estimating its construct validity through confirmatory factor analysis and assessing reliability using McDonald's omega. One hundred and twenty individuals diagnosed with diabetes mellitus, receiving care at primary health centers in Yogyakarta City, participated in this study. Data were collected using the Rosenberg Self-Esteem Scale. The estimation of validity and reliability was conducted using the JAMOVI software. Results show nine items of the Rosenberg Self-Esteem Scale demonstrate acceptable validity and reliability for measuring self-esteem among patients with diabetes mellitus. Consequently, the scale may be appropriately applied in diabetes management at primary health care settings.